Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Karyawan Bakpia Pathok 25 Yogyakarta - Faiz Fahmi Ramadhan; Bangun Putra Prasetya (Institut Nalanda, 2024)
Human Resources is organizational management that manages human elements well which is useful for maintaining a good workforce. HR is the key to the success of an organization in a company. Culture and communication are one of the keys to forming quality human resources. Employee performance is something that must be known and informed to certain parties in order to achieve work goals. Organizational culture is a bridge to create good employee performance. With the existence of an organizational culture, a group will be able to increase the values, beliefs, norms and assumptions that already apply. So that a group carries out a performance in one way or with the same vision. Communication is one of the media needed to shape good employee performance through quality human resources. With communication, the vision carried out while working will be in line. Based on this article, organizational culture and communication apparently have an impact on employee performance.